Constructing of Penta Helix Model Approach in Reducing Stunting and Upscaling Human Resource Capabilities in Surabaya Development : A Meta Synthesis - Utomo, Priyo; Pratama, Devangga Putra Adhitya; Arifin, Syamsul; Waloyo; Sandyawati, Novi Sri (Review of Management and Entrepreneurship, 2025)
This research investigates the application of the Penta Helix Model in addressing two critical issues in Surabaya City: reducing stunting and upscaling human resource capabilities. The Penta Helix Model, which encompasses collaboration among academia, business, government, community, and media, offers a comprehensive framework for sustainable urban development. Meta synthesis as this research method reffered to synthesizes findings from recent and past research to identify effective strategies and their interrelationships within this model. Key strategies for reducing stunting include nutritional interventions such as micronutrient supplementation and fortification of staple foods, health care initiatives like the Integrated Management of Childhood Illness (IMCI) and growth monitoring, and educational programs that emphasize school-based nutrition and WASH (Water, Sanitation, and Hygiene) education. Community engagement through initiatives like Community-Led Total Sanitation (CLTS) and women's empowerment programs further supports these efforts, while effective governance and supportive policies provide the necessary environment for successful implementation. In upscaling human resource capabilities, the research highlights the importance of educational enhancement through vocational training and continuing professional development, health and wellness programs to maintain a productive workforce, and community empowerment via technology-driven approaches such as AI for socio-economic predictions. Business and economic development initiatives, coupled with technological innovations like mHealth solutions and remote sensing, are also crucial in aligning workforce skills with market demands and improving access to essential services. The research finding referred the interconnectedness of these strategies and the necessity of a collaborative approach within the Penta Helix Model. By leveraging the strengths of each stakeholder, Surabaya City can develop and implement comprehensive, inclusive, and sustainable interventions to address stunting and enhance human resource capabilities. This integrated approach not only improves public health and educational outcomes but also drives economic growth and resilience, contributing to the overall development of Surabaya City